ENZYMATIC KINETIC DERACEMIZATION OF FLUORINE-CONTAINING 3-ARYLALKANOIC ACIDS - Kolodiazhna, A.О.; Faiziev, O.; Kolodiazhnyi, O.I. (Reports of the National Academy of Sciences of Ukraine, 2023)
Enantiomerically pure fluorine-containing 3-arylalkanoic acids were obtained by enzymatic hydrolysis of racemic esters of these acids. Optimization of the deracemization process was achieved by the selection of biocatalysts, acylating reagents, and temperature. The influence of the conditions of the deracemization process and the structure of the substrates on the efficiency of the biocatalytic resolution was also studied. As a result, fluorine-containing 3-arylalkanoic acids of (S)- and (R)-absolute configuration of high stereochemical purity were obtained. After the kinetic resolution the enantiomeric purity of the products attained 99 % еe.